1995
DOI: 10.1038/sc.1995.84
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging and duration of disability on long term health outcomes following spinal cord injury

Abstract: The purpose of the study was to discover the independent and combined effects of age and duration of injury on selected long term health outcomes of 83 spinal cord injured (SCI) men (age range 21-79 years; duration of spinal cord injury 3-52 years) _ Specifically, the study examined a multivariate model which specified that age, duration, the interaction of age and duration, and level of lesion were related to the following health outcomes: pain, fatigue, functional independence, mobility, illness and symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 27 publications
4
60
3
1
Order By: Relevance
“…This finding supports the descriptive reports found in the literature 1,7,[10][11][12][13] and confirms that fatigue is prevalent and of considerable concern in SCI. In persons already living with neurological impairment due to SCI, the additional impairment of fatigue could further limit activity and restrict participation in work, leisure and social activities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding supports the descriptive reports found in the literature 1,7,[10][11][12][13] and confirms that fatigue is prevalent and of considerable concern in SCI. In persons already living with neurological impairment due to SCI, the additional impairment of fatigue could further limit activity and restrict participation in work, leisure and social activities.…”
Section: Discussionsupporting
confidence: 92%
“…6 Studies in Parkinson's and stroke have shown that fatigue can be distinguished from depression both in samples that have and have not controlled for depression. 1,6 Fatigue has been reported as an issue for people with spinal cord injury (SCI); [10][11][12][13] however, estimates on the prevalence of fatigue in this population and identification of the variables that explain the presence of fatigue severity are not clearly delineated in the literature. For example, some clinical variables such as chronic pain and sleep disturbance and various demographic factors such as sex, country of residence and age have been found to be associated with fatigue after SCI, 11,12,14,15 yet little is known about the independent contributions in explaining fatigue among these variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of an individual's satisfaction with their health, family relations, friendships, employment and finance, as well as sexual life and leisure time 31,32 is often used to assess subjective QOL. 33 Social role functioning and interactions with family and friends are likely to be of high significance to an individual; 34 therefore, measures of QOL cover content similar to the core aspects of social participation measures (ie role performance and social relationships) 1 Due to their relevance to social participation and handicap, subjective QOL measures can therefore also be considered when assessing community needs.…”
Section: Measurement Of Community Needsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] In their 1990 study, DeVivo et al 11 examined the influence of age at SCI on rehabilitation outcomes. It was found that individuals who were at least 61 years old at the time of injury were more likely to have developed pneumonia, experience a gastrointestinal hemorrhage, develop pulmonary emboli and have renal stones prior to their first discharge than individuals who were 16-30 years at the time of injury.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%